2015 48th Hawaii International Conference on System Sciences 2015
DOI: 10.1109/hicss.2015.23
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Information and Communication Technologies in University Students' Learning Experience: The Instructors' Perspective

Abstract: This paper reports on a study that was undertaken to measure university instructors' perceptions of pedagogical use of various information and communication technologies (ICTs) and links these to their perceptions of effectiveness of students' learning experiences. Using a theoretically derived 54-item instrument and a rigorous probabilistic sampling strategy, survey data were collected from 2,626 instructors from 12 participating universities in Québec, Canada. Exploratory factor analyses and regression mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 34 publications
(30 reference statements)
1
14
0
Order By: Relevance
“…is study seeks to ascertain how school administrations, faculty, and ICT teams deploy computers or ICT devices on various platforms. Although the study does not focus on the impact of ICT on the achievement of students, it approaches the subject under study from the perspective of teachers and their perception about the impact of ICT on students' performance [12]. Similarly, Cruz-Jesus et al [13] analyze several studies related to the impact that ICT has made on educational institutions in Europe.…”
Section: Literature Reviewmentioning
confidence: 99%
“…is study seeks to ascertain how school administrations, faculty, and ICT teams deploy computers or ICT devices on various platforms. Although the study does not focus on the impact of ICT on the achievement of students, it approaches the subject under study from the perspective of teachers and their perception about the impact of ICT on students' performance [12]. Similarly, Cruz-Jesus et al [13] analyze several studies related to the impact that ICT has made on educational institutions in Europe.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Apart from the unassailable presence and use of Wikipedia by students and teachers alike, the potential benefits students can derive from using wiki interfaces are being much lauded (Croteau, Venkatesh, Beaudry, & Rabah, 2015;Venkatesh, Croteau, & Rabah, 2014). In a study evaluating the use of wikis in universities, Schwartz, Clark, Cossarin, and Rudolph (2004) portrayed wikis as user-friendly and offering greater flexibility than blogs; the 24 wikis evaluated in this study were mostly designed to create communal repositories of knowledge as well as allow students to discuss course-related material.…”
Section: Use Of Wikis In Higher Educationmentioning
confidence: 99%
“…As noted earlier, a digital index report on the differences across sectors and professional disciplines indicated a low ranking for the educational sector (Manyika, 2015). In higher education, a Canadian study (Croteau et al, 2015) reported disciplinary differences in ICT integration in teaching and learning. Therefore, we wanted to examine whether differences exist among several professional disciplines, ranging from education and arts and humanities to business and law and to engineering and math and ICTs.…”
Section: Hypothesesmentioning
confidence: 99%
“…Prosser and Trigwell (2000) contended that students' perception of the higher education learning environment should guide teachers' pedagogical decisions because students' perceptions are critical in their academic success. However, Croteau, Venkatesh, Beaudry, and Rabah (2015) identified a gap between teachers' and students' perceptions about the contribution of ICTs to learning, and Hammond (2014) determined a gap between rhetoric and reality in terms of studentcentered pedagogy in technology integration. A variety of reasons are reported for this:…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation